Currency and Competence of Occupational Therapists and Consumers with Rapidly Changing Technology - Emily J. Steel; Ricky Buchanan; Natasha Layton; Erin Wilson (Hindawi-Wiley, 2017)
Assistive technology was once a specialised field of practice, involving products designed for populations with specific impairments or functional goals. In Australia, occupational therapists have, at times, functioned as gatekeepers to public funding, prescribing products from a predefined list. An expanding range of accessible mainstream products available via international and online markets has changed the meaning and application of assistive technology for many people with disability. In the policy context of consumer choice and cost-effectiveness, have occupational therapists been left behind? This paper describes the change in context for access to assistive technology resulting in expanded possibilities for participation and inclusion. A case study of environmental control systems is used to explore the overlap of mainstream and assistive products and the funding and services to support their uptake. The analysis describes a future policy and practice context in which assistive technology includes a spectrum of products decoupled from access to independent advice and support services. A broader scope of occupational therapy practice has potential to enhance the occupational rights of people with disability and the efficiency and effectiveness of assistive technology provision.